Analytical model of self-acting journal bearing subjected to base excitation for marine engine system. (May 2013) - Zhang, Guanghui; Liu, Shupeng; Cao, Zhixuan; Ma, Ruixian; Liu, Zhansheng
Rotating machinery in marine engine systems experiences the base excitation from the vertical and horizontal swing movements of the ship. Too large a base motion can produce severe rotor–bearing system damage. The Reynolds equation including the effects of the base excitation on motion is derived, and the corresponding analytical model of nonlinear oil-film force based on the long- and short-length bearing assumptions is established in this article. The pressure distribution and nonlinear oil-film force of journal bearing with different forms of foundation movement are simulated by numerical simulation. The following three cases are studied: journal spin motion, journal circular whirl, and journal radial motion (pure squeeze). It indicates that foundation movement will remarkably affect the pressure distribution and nonlinear oil-film force of journal bearing, which cannot be ignored during analyzing the dynamics of journal bearing–rotor system for marine engine. This study will make the foundation for the dynamic study of rotor–bearing system considering the basement motion.